Post-COVID-19 organizational resilience in the manufacturing and service industries - Suguna Sinniah; Mansoor Ahmed Soomro; Rawshdeh, Mustafa; Mara Ridhuan Che Abdul Rahman; Kamarudin Abdul Kadir; Ainul Huda Jamil (Penerbit Universiti Kebangsaan Malaysia, 2022)
COVID-19 has shaken the business industry and forced a revisit of the resilience literature. Though organizations’ management have adopted measures prescribed by the literature, these measures have been unable to provide a fitfor-all solution. This has motivated this study to re-examine the organizational resilience factors driving operational performance in the post-pandemic era, specifically in consideration of the role of firm industry orientation and firm size. Thus, the preset study aims it to identify to what extent the organizational resilience (ability, adaptability, agility and flexibility) effects the operational performance; and, to determine how the firm size influence the relationship between organizational resilience and the operational performance of the manufacturing and service sectors. Data was collected from 85 organizations in the Malaysian manufacturing and services industries and analyzed using PLS-SEM. The results show that the agility and flexibility dimensions of resilience have a significant positive effect on operational performance, while the ability and adaptability dimensions have no such effect. Additionally, firm size was found to be insignificant in the relationship between organizational resilience and operational performance. The findings reveal that resilience is vital for the sustainability of an organization in this turbulent and complex business climate. Therefore, managers should thus consider incorporating appropriate resilience strategies in both opportunities and operations to embrace different strategies to leverage organizational resilience post COVID. Ultimately, the government should utilize these findings for policymaking when leading post-COVID-19 projects and initiatives.